Pengaruh Gaya Hidup Hedonis Dan Flash Sale Terhadap Perilaku Impulsive Buying Generasi Z Pada Platform E-Commerce Shopee (Studi Mahasiswa Febi Uin Sultan Thaha Saifuddin Jambi) - Zahrotul Aini; Eja Armaz Hardi; Aztyara Ismadharliani (JOURNAL OF SHARIA ECONOMICS, 2025)
The rapid development of digital technology and e-commerce has significantly transformed consumer behavior, particularly among Generation Z, a demographic known for its strong engagement with digital platforms and online shopping activities. Various digital marketing strategies implemented by e-commerce platforms, such as flash sales, along with the growing tendency toward a hedonic lifestyle, are believed to contribute to the emergence of impulsive buying behavior. This study aims to examine the influence of hedonic lifestyle and flash sales on impulsive buying behavior among Generation Z Shopee users. The research employed a quantitative approach with a causal associative design. Data were collected through questionnaires distributed to 95 students of the Faculty of Islamic Economics and Business at UIN Sulthan Thaha Saifuddin Jambi, selected using a purposive sampling technique. Data analysis was conducted using multiple linear regression with the assistance of IBM SPSS Statistics software. The results revealed that hedonic lifestyle has a positive and significant effect on impulsive buying behavior, with a significance value of 0.000 (< 0.05). Similarly, the flash sale variable also demonstrated a positive and significant effect on impulsive buying, with a significance value of 0.009 (< 0.05). Simultaneously, hedonic lifestyle and flash sales significantly influence impulsive buying behavior, as indicated by a coefficient of determination (R²) of 0.52. This finding suggests that both variables explain 52% of the variance in impulsive buying behavior, while the remaining 48% is influenced by other factors beyond the scope of this study. These findings indicate that impulsive purchasing behavior among Generation Z is shaped by the interaction of internal factors, represented by a hedonic lifestyle, and external factors, represented by flash sale promotional strategies. Therefore, enhancing financial literacy and self-control is essential to prevent excessive consumptive behavior in the digital shopping environment.